2009
DOI: 10.1074/jbc.m804178200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyaluronic Acid on Mitochondrial Function and Mitochondria-driven Apoptosis following Oxidative Stress in Human Chondrocytes

Abstract: Hyaluronic acid is widely used in the treatment of osteoarthritis and exerts significant chondroprotective effects. The exact mechanisms of its chondroprotective action are not yet fully elucidated. Human articular chondrocytes actively produce reactive oxygen and nitrogen species capable of causing cellular dysfunction and death. A growing body of evidence indicates that mitochondrial dysfunction and mitochondrial DNA damage play a causal role in disorders linked to excessive generation of oxygen free radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 32 publications
7
100
0
Order By: Relevance
“…Hyaluronic acid, which is essential for the maintenance of synovial joints, has recently been shown to have a protective effect for radical-induced mitochondrial DNA damage (25). In this scenario, hyaluronic acid may be utilized by mitochondria damaged by fluoroquinolone exposure, thereby creating a shortage of hyaluronic acid at the articular surface of the joint.…”
Section: Fluoroquinolones and Chondrotoxicitymentioning
confidence: 99%
“…Hyaluronic acid, which is essential for the maintenance of synovial joints, has recently been shown to have a protective effect for radical-induced mitochondrial DNA damage (25). In this scenario, hyaluronic acid may be utilized by mitochondria damaged by fluoroquinolone exposure, thereby creating a shortage of hyaluronic acid at the articular surface of the joint.…”
Section: Fluoroquinolones and Chondrotoxicitymentioning
confidence: 99%
“…Hyaluronan is an essential component of the extracellular matrix and is involved in important physiological functions, such as cell-to-cell identification, cellular cohesion, growth regulation, and antioxidant capacity [14] . Its combination with LAs may also ameliorate apoptotic cell death and enhance cell survival in chondrocytes [15,16] . However, the precise mechanisms of hyaluronan actions, especially those associated with cytoprotection, have not been firmly established, despite its widespread use in outpatient clinics.…”
Section: Wwwchinapharcom Lee Yj Et Almentioning
confidence: 99%
“…Moreover, that study also showed that OA chondrocytes exposed to a high, hyperglycemia-like extracellular glucose concentration (30 mM) were unable to reduce glucose transport and GLUT-1 content which led to increased glucose accumulation and prolonged Reactive Oxygen Species (ROS) production [Rosa et al, 2009]. Increased oxidative stress has been pointed out as a major pathogenic mechanism of OA [Maneiro et al, 2003;Grishko et al, 2009], and at the cellular level, increased ROS production has been shown to mediate many catabolic responses in chondrocytes [Lo et al, 1998; Mendes et al, 2003a,b].…”
Section: Abstract: Collagen; Gene Expression; Glucose; Human Chondromentioning
confidence: 97%
“…Moreover, that study also showed that OA chondrocytes exposed to a high, hyperglycemia-like extracellular glucose concentration (30 mM) were unable to reduce glucose transport and GLUT-1 content which led to increased glucose accumulation and prolonged Reactive Oxygen Species (ROS) production [Rosa et al, 2009]. Increased oxidative stress has been pointed out as a major pathogenic mechanism of OA [Maneiro et al, 2003;Grishko et al, 2009], and at the cellular level, increased ROS production has been shown to mediate many catabolic responses in chondrocytes [Lo et al, 1998; Mendes et al, 2003a,b].Thus, this study was undertaken to determine whether exposure to a high extracellular glucose concentration can shift normal and OA chondrocyte functions towards a pro-catabolic and/or antianabolic gene expression profile, either direct or indirectly by modifying the responses induced by pro-anabolic stimuli, namely TGF.For this purpose, we examined by real time RT-PCR (qRT-PCR) the expression of genes that are important for cartilage homeostasis and OA pathogenesis and that in other cell types have been reported to be modulated by exposure to high glucose [Death et al, 2003;Ho et al, 2007;Andreea et al, 2008;Kim et al, 2008]. Those genes include the MMPs-1 and -13 due to their major role in cartilage matrix degradation, and collagen type II, TIMP-1 and TIMP-2 as important anabolic and anti-catabolic genes, respectively.…”
mentioning
confidence: 97%